Determinants of Economic Growth in ASEAN-5: The Role of Foreign Direct Investment, Government Expenditure, and Per Capita Income - Ammar, Hafiz; Purnomo, Didit (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effects of Foreign Direct Investment (FDI), government expenditure, and per capita income on economic growth in ASEAN-5 countries during the 2019–2024 period. The study employs a quantitative approach using panel data regression analysis covering Indonesia, Malaysia, Singapore, Thailand, and Vietnam. Secondary data were obtained from the World Development Indicators (WDI) database published by the World Bank. The analytical methods applied include the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM), with the FEM selected as the most appropriate model based on the Chow and Hausman tests. The findings indicate that FDI has a positive effect on economic growth, suggesting that foreign investment contributes to production expansion, technology transfer, and job creation in ASEAN-5 countries. In contrast, government expenditure exerts a negative effect on economic growth, indicating inefficiencies in public spending allocation during the post-pandemic recovery period. Meanwhile, per capita income does not have a significant effect on economic growth. This study provides empirical evidence regarding the dynamics of economic growth in the post-pandemic era and offers policy implications for strengthening inclusive and sustainable economic development strategies in the ASEAN region.